Changes in cerebral function parameters in HIV-1 infected subjects undergoing a treatment simplification to darunavir/ritonavir - Garvey, LJ; Higgs, C; Mohammed, P; Nelson, M; Winston, A (Journal of the International AIDS Society, 2010)
7‐11 November 2010, Tenth International Congress on Drug Therapy in HIV Infection, Glasgow, UK